MINIMUM LEVELS AND FRAMING IN PUBLIC GOOD PROVISION. (1st March 2019) - Martinsson, Peter; Medhin, Haileselassie; Persson, Emil
Abstract : Using a laboratory experiment in the field, we examine how the framing of a social dilemma, give to or take from a public good, interacts with a policy intervention that enforces a minimum contribution level to the public good. We find significantly higher cooperation in the give frame than in the take frame in our standard public goods experiment. When a minimum contribution level is introduced, contributions are crowded out in the give frame but crowded in in the take frame. Our results show the importance of choosing the frame when making policy recommendations. ( JEL C91, H41)